Effect of lite touch on the anxiety of low-risk pregnant women in the latent phase of childbirth: a randomized controlled trial - Yang, Wenqian; Wang, Yonghong; Ko, Chingyuan; Niu, Xiaoyu; Huang, Yan; Luo, Biru; Wang, Guoyu; He, Jingjing; Li, Huafeng (Frontiers in Psychology, 2024)
Introduction Women with perinatal anxiety have reduced coping capacity during labor, which affects labor progress and increases the likelihood of a cesarean section. Several non-pharmacological interventions for anxiety during childbirth are available. This study used the “lite touch” method, a non-pharmacological intervention based on physiological responses and obstetric clinical experience in women. We aimed to evaluate whether lite touch could relieve perinatal anxiety and investigate the effect of light skin stroking on the maternal hormones, catecholamine, and cortisol. Methods This randomized clinical trial involved women with low-risk singleton pregnancies at full term or near term. Eligible pregnant women who were latent and did not undergo epidural anesthesia were randomized into two groups. Participants in the intervention group underwent routine prenatal care, including lite touch, whereas the control group underwent routine prenatal care alone. Demographic data were collected through a questionnaire. Labor anxiety was assessed using the State Anxiety Inventory, and saliva was collected before and after the intervention. Changes in saliva cortisol and catecholamine levels were analyzed using a double-antibody sandwich enzyme-linked immunosorbent assay. Results In total, 83 participants were included, with 43 and 40 in the intervention and control groups, respectively. In the intervention group, pre-intervention anxiety scores were significantly lower (p < 0.01) than post-intervention anxiety scores, whereas the control group showed no difference in anxiety scores before and after intervention (p > 0.05). Cortisol and catecholamine levels in saliva were significantly lower in the intervention group than in the control group after the intervention (p < 0.01). Discussion Lite touch can reduce the latent anxiety state of low-risk pregnant women, thereby maintaining in vivo stability and facilitating labor. Clinical trial registration https://www.chictr.org.cn/aboutEN.html, ChiCTR2300070905, Retrospectively Registered Date: April 26, 2023.